Pengenalan Morfologi Dan Anatomi Ikan Untuk Meningkatkan Wawasan Dan Minat Makan Ikan Anak Usia Dini - Nurul Mutmainnah; Rismawaty Rusdi; Yusdalifa Ekayanti Yunus Yunus; Ummu Kaltsum SC; Fitri Indah Yani; Adi Irwandi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity was carried out in November 2022. The target are students at Aisyiyah Kindergarten Jampue Branch who are classified as Early Childhood Children. The method used is sharing and practice introducing morphology and anatomy of goldfish (Cyprinus carpio). The activity was carried out in several stages, namely: the initial stage in form of obtaining permits from the school, then the implementation stage by interacting with students to introduce fish morphology, and practice introducing fish anatomy by directly fish surgery. This service activity succeeded in increasing understanding and enthusiasm of Aisyiyah Kindergarten students, Jampue Branch, to learn more about the morphology and anatomy of fish. Apart from that, this activity provides information to students about the benefits of fish as food with the various advantages that fish has.